MINIMIZING IMPLANT FAILURES - SAREEN, DR. SAKSHI; SHAH, DR. JAYATI (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Despite significant advances in devices and techniques, placement of dental implants at a correct position as per the esthetic, biological, and functional perspective still remains a challenge, because the trajectory of implants is seldom consistent with that of natural teeth due to the bone loss that follows extraction. Computerized‑implant‑dentistry being highly predictable and minimally invasive in nature has also allowed implant placement in patients with medical comorbidities (e.g. radiation therapy, blood dyscrasias), in patients with complex problems following a significant alteration of the bony anatomy as a result of benign or malignant pathology of the jaws or trauma and in patients with other physical and emotional problems. With significant achievements accomplished in the field of computerized implant‑dentistry, attempts are now been made toward complete automation of implant‑dentistry.